Callus Induction from leaf explants of Mas Cotek (Ficus Deltoidea var. bilobata) treated with 6-Benzylaminopurine (BAP) and 4-Amino-3, 5, 6-Trichloropicolinic acid (Picloram) - Ismail, Azrina; Shahidan, Norshazila; Othman, Rashidi; Mat, Nashriyah (Science Publishing Corporation Inc, 2018)
The objective of this study was to observe the effect of 6-Benzylaminopurine (BAP) and 4-Amino-3, 5, 6-trichloro picolinic acid (Picloram) on callus induction of Mas Cotek (Ficus deltoidea var bilobata) explant. Murashige and Skoog (MS) nutrient media supplemented with 6-Benzylaminopurine (BAP) and 4-amino-3,5,6-trichloro picolinic acid (Picloram) each at different concentrations of 0 mg/l, 0.5 mg/l , 1.5 mg/l and 3.0 mg/l, respectively. The control and other six treatments gave negative responses to the MS media supplemented with various concentrations of BAP and Picloram. Most of the callus began to form at day 16 up to day 30 with treatment. Hard and yellowish callus with moderate growth rate was obtained from explants cultured on MS medium supplemented with 0.5 mg/ l BAP and 1.5 mg/l Picloram, wherein the callus formation was recorded at 47 %. Hard and greenish callus was obtained from medium treated with 0.5 mg/l BAP and 0.5 mg/l Picloram after 30 days of treatment with callus formation of 26.67 %. Medium supplemented with 0.5 mg/l of BAP hormone and 1.5 mg/l of Picloram hormone displayed the best growth rate of callus and was the most suitable medium for callus induction.